Modeling C3 glomerulopathies: C3 convertase regulation on an extracellular matrix surface - Pisarenka, Sofiya; Meyer, Nicole C.; Xiao, Xue; Goodfellow, Renee; Nester, Carla M.; Zhang, Yuzhou; Smith, Richard J. H. (Frontiers in Immunology, 2023)
Abstract C3 glomerulopathies (C3G) are ultra-rare complement-mediated diseases that lead to end-stage renal disease (ESRD) within 10 years of diagnosis in ~50% of patients. Overactivation of the alternative pathway (AP) of complement in the fluid phase and on the surface of the glomerular endothelial glycomatrix is the underlying cause of C3G. Although there are animal models for C3G that focus on genetic drivers of disease, in vivo studies of the impact of acquired drivers are not yet possible. Here we present an in vitro model of AP activation and regulation on a glycomatrix surface. We use an extracellular matrix substitute (MaxGel) as a base upon which we reconstitute AP C3 convertase. We validated this method using properdin and factor H (FH) and then assessed the effects of genetic and acquired drivers of C3G on C3 convertase. We show that C3 convertase readily forms on MaxGel and that this formation was positively regulated by properdin and negatively regulated by FH. Additionally, Factor B (FB) and FH mutants impaired complement regulation when compared to wild type counterparts. We also show the effects of C3 nephritic factors (C3Nefs) on convertase stability over time and provide evidence for a novel mechanism of C3Nef-mediated C3G pathogenesis. We conclude that this ECM-based model of C3G offers a replicable method by which to evaluate the variable activity of the complement system in C3G, thereby offering an improved understanding of the different factors driving this disease process.